2006
DOI: 10.1111/j.1471-0307.2006.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

How hygiene happens: physics and chemistry of cleaning

Abstract: Cleaning is a commonplace but poorly understood operation in the dairy industries. This paper describes recent work to identify and quantify the critical factors that control cleaning. Experiments have used micromanipulation probes to remove deposits from surfaces; these probes can measure the force required to remove deposits, and allow simple models of cleaning to be produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 42 publications
1
39
0
8
Order By: Relevance
“…In dairy plants, water consumption levels are determined by production output and the applied technologies. The implementation of adequate production hygiene standards, the need to reduce water consumption and increase the effectiveness of wastewater treatment in various branches of the food processing industry have been discussed by numerous authors [9][10][11][12][13][14][15][16] . The microbiological quality of milk determines the range of heat treatments in a dairy plant, and it affects the usage of cooling water in heat exchangers and the consumption of cleaning water.…”
Section: Introductionmentioning
confidence: 99%
“…In dairy plants, water consumption levels are determined by production output and the applied technologies. The implementation of adequate production hygiene standards, the need to reduce water consumption and increase the effectiveness of wastewater treatment in various branches of the food processing industry have been discussed by numerous authors [9][10][11][12][13][14][15][16] . The microbiological quality of milk determines the range of heat treatments in a dairy plant, and it affects the usage of cooling water in heat exchangers and the consumption of cleaning water.…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning efficiency coefficients for these programs were in range of 1.25 -1.96. Thus, increase in the flow rate during the cleaning process not only improves the cleaning efficiency, as observed by other authors (Goode et al, 2010;Fryer et al, 2006), but also affects the reduction of costs associated with performance of the process with simultaneous decreasing of the temperature of cleaning agents.…”
Section: Analysis Of the Efficiency Of Cleaning In Relation To Total mentioning
confidence: 56%
“…When interpreting this result, we can conclude that with increase in the amount of electricity consumed for heating rinsing water, the efficiency of removal of milk residues from the installation decreases. Properties of milk residues may be an explanation for that phenomenon as they are not dissolved in high temperature of the cleaning liquid (Almecija et al, 2009;Changani et al, 1997;Fryer et al, 2006). Analysis of the study results also showed that with an increase in the electricity necessary for the operation of the impeller pump, effectiveness of the heat exchanger cleaning is increasing.…”
Section: Analysis Of the Efficiency Of Cleaning In Relation To Total mentioning
confidence: 68%
“…Knowledge about water quality of a water stream is important, when a stream is to be reused or recycled in the plant (Fryer, P. J., Christian, G. K. & Liu, W., 2006;Casani, S., Rouhany, M. & Knøchel, S., 2005;Rad and Lewis, 2014). In the present project, the water quality of the water streams to be reused or recycled was not tested, except for cow water.…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 99%